Pengaruh Struktur Modal, Company Size, dan Kinerja Keuangan Terhadap Agresivitas Pajak - Afghoni, Lazuardi Hasan; Ismanto, Juli (TIN: Terapan Informatika Nusantara, 2025)
This study was conducted to examine and provide empirical evidence regarding the influence of capital structure, company size and financial performance on tax aggressiveness in non-cyclical consumer sector companies recorded on the IDX for the 2020-2024 period. This study takes a quantitative approach by utilizing secondary data as a source of information. The sample was 37 companies selected through purposive sampling during five years of observation. Data analysis uses panel data regression with the help of the EViews version 13 program. The variables studied include capital structure (X1), company size (X2), financial performance (X3), and tax aggressiveness (Y). The study results indicate that the best model is the Fixed Effect Model (FEM). From the results of the analysis, simultaneously capital structure, company size and financial performance are proven to influence tax aggressiveness as indicated by the F-statistic probability value of 0.000000 < 0.05. Partially, capital structure is proven to influence tax aggressiveness as indicated by a probability value of 0.0280 < 0.05, and financial performance is also proven to influence tax aggressiveness as indicated by a probability value of 0.0015 < 0.05, while company size has no influence on tax aggressiveness as indicated by a probability value of 0.3855 > 0.05. The coefficient of determination value is 56.10%, which means the remaining 43.90% is influenced by other variables outside this study.